Practice of an ukemi drill game with young judo athletes: Effectiveness of video shown on a tablet - Ozawa, Y.; Mishima, E.; Kiyota, K.; Mitsuda, R.; Nakamura, I.; Hamada, H.; Ishibashi, G.; Ohkawa, Y.; Sakamoto, M.; Nakahara, H. (Association for the Scientific Studies on Judo, Kodokan, 2021)
This study aimed to investigate the effectiveness of visually demonstrating the correct "roll direction" for a "mae mawari ukemi" using the usual explanation and demonstration by an instructor with the new addition of a short video shown on a tablet as well as the practice of the ukemi drill game designed by Ozawa et al. in young judo athletes.The results are as follows: 1. Approximately 73% of "mae mawari ukemi" and 86% of "usiro ukemi" matches were decided by differences in score demonstrating a relatively high game-like quality and revealing that the difficulty level of both ukemi drill games was consistent.2. Visually demonstrating the correct "roll direction" for a "mae mawari ukemi" using the usual explanation and demonstration by an instructor with the new addition of a short video shown on a tablet was effective, regardless of grade level.3. When students were only provided with the usual explanation and demonstration by an instructor for a "usiro ukemi," girls were less able than boys to master the correct "head position and gaze," thus identifying a new challenge.